Revisiting selective nucleation at heterophase interfaces in Fe–Al solid-liquid reaction - Qun Luo; Wei Liu; Weihao Li; Qinfen Gu; Binjun Wang; Qian Li (Journal of Materials Research and Technology, 2022)
The reaction between solid Fe and liquid Al occupies the important position due to its wide application in industrial processes. However, it is still unclear now which intermetallic compounds will form and the formation mechanism of Fe–Al intermetallic phases. In present work, the Fe–Al solid-liquid reaction by using iron wire as Fe resource is traced by in-situ synchrotron powder X-ray-diffraction. With Fe4Al13 as the dominant phase, two intermetallic phases named Fe4Al13 and Fe2Al5 are found. This phenomenon is different with the result obtained from the diffusion couple of Fe block and melt Al. Thermodynamic calculation and molecular dynamics simulation are performed to verify the underlying mechanism. Related events such as interfacial diffusion and nucleation driving force are analyzed and discussed.